Bipolar bioelectrical impedance: lack of accuracy in estimating relative body fat in men. DOI: 10.5007/1980-0037.2011v13n2p100 - Maria Fatima Glaner; Cassiano Ricardo Rech (Universidade Federal de Santa Catarina, 2011)
Bioelectrical impedance (BI) is commonly used to estimate body composition in different populations. The aim of this study was to determine the accuracy of bipolar BI (Omron BF 300) in estimating relative body fat (%F) by comparing it with dual-energy X-ray absorptiometry (DEXA). %F was measured in 66 men (18 to 33 years) with a mean body weight of 73.7 ± 8.4 kg, height of 175.1 ± 6.5 cm, body mass index of 23.9 ± 2.2 kg/m2, %FBI 15.1 ± 4.4%, and %FDEXA 17.7 ± 5.1%. A paired t-test, correlation test, standard error of the estimate (SEE), and residue analysis were used to evaluate the accuracy of the method. BI significantly (p < 0.05) underestimated %F and, the correlation between the two methods was moderate (r = 0.769). Residue analysis showed the lack of agreement between the two methods, with an average error of -2.6 percentage points (95%CI: -9.1; 3.9). The SEE was above the recommended level (>3.5%F) in 42% of the sample. In subjects with higher fat accumulation (%F >20%), the Omron BF BI model produced greater bias in the %F measurement. Therefore, in the case of adult men, the Omron BF 300 BI model does not agree with the DEXA measurement for the estimation of %F in adult men. In addition, the higher the level of fat accumulation, the higher the error in estimated %F.